Nutrient effect of various composting methods with and without biochar on soil fertility and maize growth. Issue 2 (28th January 2020) - Pandit, Naba Raj; Schmidt, Hans Peter; Mulder, Jan; Hale, Sarah E; Husson, Olivier; Cornelissen, Gerard
ABSTRACT: This work showed for the first time that organic nutrient transformation techniques based on locally available materials (manure, green waste and advanced biochar) can increase fertilizing efficiency of the resulting substrate by a factor of three compared with other organic amendments without biochar. We used three different composting methods to investigate the techniques of organic nutrient transformations; i) conventional composting (composting process completed without turning the piles) ii) aerobic composting (composting process with manual turning of piles) and iii) bokashi composting (anaerobic lacto-fermentation). Composting was carried out in the absence (compost alone) and the presence of biochar (co-composted). Biochar was produced locally from an invasive forest shrub ' Eupatorium adenophorum '. A pot trial with maize grown in silty loam soil was carried out to investigate the agronomic effect produced using three above-mentioned composting methods that were compared with conventional mineral fertilizers (NPK). Significant effects of co-composted bokashi-biochar (60 t ha −1 ) were observed on maize growth, which increased biomass by 243% compared to mineral NPK, also showing better growth effects than conventional and aerobic composting amendments. Improved soil available nutrients (available P and other exchangeable base cations (K +, Ca 2+ and Mg 2+ )) were probably the cause of the superior growth effect of co-composted bokashi-biochar.